The Effect of Lipid Metabolism on CD4+ T Cells - Feiyang Cai; Shuxin Jin; Guangjie Chen (Hindawi Limited, 2021)
CD4+ T cells play a vital role in the adaptive immune system and are involved in the pathogenesis of many diseases, including cancer, autoimmune diseases, and chronic inflammation. As an important mechanism for energy storage, a lot of researches have clarified that metabolism imbalance interacts with immune disorder, and one leads to the other. Lipid metabolism has close relationship with CD4+ T cells. In this review, we discuss fatty acid, cholesterol, prostaglandin, and phospholipid metabolism in CD4+ T cell subsets. Fatty acid β-oxidation (FAO) is activated in Th17 cell to support the proinflammatory function. Cholesterol promotes Th1, Th2, and Treg cell differentiation. In addition to glucose metabolism, lipid metabolism is also very important for immunity. Here, it is highlighted that lipid metabolism regulates CD4+ T cell differentiation and function and is related to diseases.